Pengaruh Motivasi, Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan : Studi pada PT Phapros Semarang - Lusia Rambu Leli; Hasan Abdul Rozak (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the influence of motivation, work discipline, and job satisfaction on employee performance at PT Phapros Tbk Semarang. The study was conducted with a quantitative approach using a survey method by distributing questionnaires to 100 respondents who are company employees. The data obtained were then analyzed using a series of statistical tests, including validity and reliability tests to ensure instrument accuracy, classical assumption tests to test model feasibility, and multiple linear regression analysis to determine the influence of each independent variable on the dependent variable. Furthermore, a t-test was conducted to test partial effects, an F-test to test simultaneous effects, and a coefficient of determination (R²) test to see the magnitude of the contribution of the independent variables to the dependent variable. The results of the analysis show that motivation, work discipline, and job satisfaction have a positive and significant effect on employee performance, both partially and simultaneously. The Adjusted R² value of 0.485 indicates that the three variables are able to explain 48.5% of the variation in employee performance, while the remaining 51.5% is influenced by other factors not examined. Of the three variables, job satisfaction has the most dominant influence with a regression coefficient value of 0.306, indicating the importance of the role of job satisfaction in improving employee performance.